Research on Building Decarbonization Technology based on Knowledge Map - Zhao Jiangrui (MATEC Web of Conferences)
Building decarbonization technologies have become increasingly important to study in recent years. ， This paper presents a Citespace-based econometric analysis of 1123 documents from the Web of Science Core Collection from 2011-2025.Revealing three main features of building decarbonization technology research：First, Chinese and British research institutions are in a dominant position in international research, reflecting strong academic influence;Secondly, the trend of interdisciplinary integration is remarkable, and the cross research between building science and energy, materials and other fields has become a hot direction;Finally, the research paradigm is shifting towards intelligent and sustainable synergies.These evolutionary trends indicate that the current research has broken through the single technology dimension and started to transform to integrated innovation and systematic solutions, providing more comprehensive technical support for the low-carbon transformation of the construction industry in the context of addressing climate change.